Chemistry, resources, anticancer effects, other pharmacological properties, and clinical trials of oleandrin from Nerium oleander: An overview - Siu Kuin Wong, Hung Tuck Chan, Eric Wei Chiang Chan (Journal of Applied Pharmaceutical Science, 2025)
This overview entails the chemistry, resources, anticancer effects, other pharmacological properties, and clinical trials of oleandrin, a major cardenolide from Nerium oleander. The highest quantity of oleandrin is in the roots followed by leaves, stems, and flowers. In its chemical structure, oleandrin contains a central steroid nucleus, a lactone structure, dideoxy arabinose or L-oleandrose group, and an acetyloxy moiety. Oleandrin has inhibitory effects against a diverse type of cancer cells with 19 types recorded in this overview. In its anticancer activities, oleandrin inhibits cell proliferation, reduces cell viability, induces apoptosis, and promotes cell cycle arrest. These activities involve the modulation of multiple cellular signaling pathways such as those of nuclear factor kappa B, mitogen-activated protein kinase, and phosphoinositide 3-kinase/protein kinase B. Anvirzel and PBI-05204 are two anticancer drugs where oleandrin is the principal bioactive component. Their clinical trials are briefly summarized. Other pharmacological properties of oleandrin include neuroprotective, anti-inflammatory, anti-osteolysis, anti-viral, anti-allergic, and toxic effects on saline organisms. Studies have shown that oleandrin, PBI-05204, a derivative of oleandrin, and PBI-04711, a fraction of PBI-05204, possess superior neuroprotective properties. Notable is their ability to penetrate the blood–brain. Fields and topics for further research on oleandrin are suggested.
Keywords: Anvirzel, PBI-05204, cardenolides, anticancer, other pharmacological properties